Analysis of Educational Values in the Novel Si Anak Savana by Tere Liye as Teaching Material for Literature Learning in High School - Muji Zain Naufal; Ade Apriyanto; Desi Ratnasari (PAEDAGOGIA, 2024)
Character education is a crucial aspect that must be imparted to pupils in schools. This is due to the fact that students, particularly adolescents, engage in a range of deviant behaviors as a manifestation of juvenile delinquency, including physical altercations, harassment, promiscuity, and similar activities. Contemporary reports in the media suggest that juvenile criminality has surpassed acceptable boundaries. The significance of character education in daily life can be exemplified through literary works, particularly novels. This research aims to analyze the educational values included in the novel "Si Anak Savana" by Tere Liye and assess the potential use of these values as teaching material for literary instruction in high school. The research employed a qualitative methodology. The research employs data collection strategies such as reading and note-taking. The analysis conducted reveals that the novel Si Anak Savana by Tere Liye encompasses fourteen educational values, namely: Religious, Honest, Disciplined, Hard Work, Creative, Independent, Democratic, Curious, Friendly, Peaceful, Passionate Reading, Environmental Care, Social Care, and Responsibility. The findings of this study serve as a resource that is anticipated to enhance understanding and can be applied in the teaching of Indonesian language to twelfth grade students, specifically in relation to the educational values. The urgency of this research is to describe the educational values in the novel "Si Anak Savana" by Tere Liye. The limitation of this research is that it is still limited to descriptive analysis and has not been carried out through experimental research to test its effectiveness